Evaluation of the Collaborative and Proactive Solutions Model in an Alternative Educational Setting - Stefan Bostrom; Martin Karlberg; Candace Schell; Nina Klang (MDPI AG, 2024)
The aim of this study was to evaluate the Collaborative and Proactive Solutions (CPS) intervention in an alternative educational setting for students with behavioural problems. The effect of the CPS intervention on students' off-task behaviour was studied using a single-subject experimental design that included two students with behavioural problems via systematic direct observations and direct behaviour ratings. The usability of the CPS intervention was investigated through questionnaires and interviews with the participating students and teacher assistant. The results revealed no significant effects of the CPS intervention on students' off-task behaviour. The students and teacher assistant viewed the CPS intervention as acceptable but the teacher assistant's ratings of the feasibility of the intervention were lower, together with the ratings of the extent to which the intervention matched the socio-political climate of the educational setting.